2018
DOI: 10.5617/adno.5643
|View full text |Cite
|
Sign up to set email alerts
|

Extensive reading in primary school EFL

Abstract: Reading in the English subject in both primary and secondary school often involves studying course book texts in detail. Therefore, pupils are rarely exposed to longer texts which require reading for meaning, a skill needed in higher education and working life. With the right reading material, extensive reading (ER) should start already in primary school. This article reports on a study of primary school pupils from three different schools and their perceptions of an extensive reading and writing project, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…It is helpful to assist some students to choose the right materials to read at the outset of an ER programme. As shown in this study and Birketveit et al’s 2018 study, some students do need help in selecting books, especially for those who have little experience of reading.…”
Section: Pedagogical Implications and Conclusionmentioning
confidence: 75%
See 1 more Smart Citation
“…It is helpful to assist some students to choose the right materials to read at the outset of an ER programme. As shown in this study and Birketveit et al’s 2018 study, some students do need help in selecting books, especially for those who have little experience of reading.…”
Section: Pedagogical Implications and Conclusionmentioning
confidence: 75%
“…More recently, Birketveit, Rimmereide, Bader, and Fisher (2018) implemented an ER programme in Norway with 83 pupils from three primary schools in order to explore the students’ perceptions of the reading materials and their attitudes towards ER. They prepared three different crates of English graded readers to circulate between three schools.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A total of 168 texts were available for the researcher's use. Because many students had low language proficiency, they did not know how to select appropriate texts for themselves (Birketveit, Rimmereide, Bader, & Fisher, 2018;Chang, 2019), so the researcher selected shorter texts for them to use in the beginning. Some 40 texts were selected, and most were nonfiction texts requiring little background knowledge to comprehend them, e.g., Good Things to Do and Eggs.…”
Section: Practice Materialsmentioning
confidence: 99%
“…While the majority of the research literature focuses on the use of extensive reading at the secondary and tertiary levels, with a number of studies focusing on students' motivation and attitudes toward reading, there are several research on EFL contexts at the elementary school level. Birketveit et al (2018) investigated the attitudes of Norwegian primary school students toward extensive reading and writing programmes at three different primary schools, as well as their responses to the provided reading materials. Their study revealed significant differences in the evaluation of reading materials between schools, as well as significant differences in the perceptions of reading materials between boys and girls (Birketveit et al, 2018).…”
Section: Research On Er In Elementary Schools In An Efl Contextmentioning
confidence: 99%